SUSTAINABILITY TRANSITION PATHWAYS OF RURAL SMES IN INDONESIA: INTEGRATING LOCAL KNOWLEDGE AND GREEN INNOVATION - Mardiatul Jannah; Agung Muliaman Anas; Pahrul (INQUISITIVE : International Journal of Economic, 2026)
Sustainability transition has become a strategic agenda for rural SMEs in Indonesia as they face increasing pressures from climate change, green market demands, and shifts in local socio-economic systems. This study analyzes the sustainability transition pathways of rural SMEs by examining the integration of local knowledge and green innovation within the socio-technical context of rural communities. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis in several rural areas with active SME ecosystems. The findings indicate that rural SMEs exhibit low to moderate levels of sustainability readiness due to limited access to technology, green financing, and institutional support. However, local knowledge serves as a key driver of eco-based innovation, including the use of natural materials, low-impact traditional production methods, and community-driven ecological practices. The integration of local knowledge and green innovation generates three transition pathways: (1) niche-led green transition pathway, driven by locally rooted innovations; (2) community-driven reconfiguration pathway, shaped by strong social networks and local institutions; and (3) hybrid technology–local wisdom pathway, combining environmentally friendly technologies with indigenous practices. This study demonstrates that sustainability transitions in rural SMEs rely not on advanced technologies but on community strength, cultural values, and contextually embedded low-cost innovations. The results contribute to the broader understanding of sustainability transitions in developing countries and offer valuable insights for designing inclusive green SME policies at the rural level.